Pengaruh Moderasi Ketidakpastian Lingkungan Pada Hubungan Antara Karakteristik Sistem Informasi Akuntansi Manajemen Terhadap Kinerja Karyawan PT. Astra Internasional, TBK Daihatsu Pontianak - Oktavina, Maria Claudia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This study aims to examine the effect of the relationship between management accounting information systems (SIAM) on employee performance which is moderated by environmental uncertainty towards employees of PT Astra International, Tbk Daihatsu Pontianak. By distributing questionnaires, 75 respondents were obtained by testing hypotheses using multiple regression analysis.The results of this study indicate (1) SIAM variables have a positive and significant effect on employee performance, (2) Environmental uncertainty which is a moderating variable is proven to strengthen the interaction between SIAM and employee performance.